Nanoporous silica entrapped lipid-drug complexes for the solubilization and absorption enhancement of poorly soluble drugs - Shin, Hey Won; Kim, Joo Eun; Park, Young Joon (Pharmaceutics, 2021)
This study aims to examine the contribution of nanoporous silica entrapped lipid-drug complexes (NSCs) in improving the solubility and bioavailability of dutasteride (DUT). An NSC was loaded with DUT (dissolved in lipids) and dispersed at a nanoscale level using an entrapment technique. NSC microemulsion formation was confirmed using a ternary phase diagram, while the presence of DUT and lipid entrapment in NSC was confirmed using scanning electron microscopy. Differential scanning calorimetry and X-ray diffraction revealed the amorphous properties of NSC. The prepared all NSC had excellent flowability and enhanced DUT solubility but showed no significant difference in drug content homogeneity. An increase in the lipid content of NSC led to an increase in the DUT solubility. Further the NSC were formulated as tablets using D-α tocopheryl polyethylene glycol 1000 succinate, glyceryl caprylate/caprate, and Neusilin®. The NSC tablets showed a high dissolution rate of 99.6% at 30 min. Furthermore, NSC stored for 4 weeks at 60◦C was stable during dissolution testing. Pharmacokinetic studies performed in beagle dogs revealed enhanced DUT bioavailability when administered as NSC tablets. NSC can be used as a platform to develop methods to overcome the technical and commercial limitations of lipid-based preparations of poorly soluble drugs.
Keywords: Dutasteride; Lipid formulation; Nanoemulsion; Nanoporous silica entrapped lipid-drug complex; Solid dosage form